A review on latest innovations in physical modifications of galactomannans - Kian-Pour, Nasim; Yildirim-Yalcin, Meral; Kurt, Abdullah; Ozmen, Duygu; Toker, Omer Said (ELSEVIER SCI LTD, 2023)
With developments in the hydrocolloid industry, modification applications based on green technologies have emerged as an important research topic to ensure the use of gums for various functional purposes in various food systems. Galactomannans are multifunctional macromolecules found in the seeds of leguminous plants. Ac-cording to their sources, which differ in the ratio of mannose/galactose units, molecular weight, and distribution of individual galactose branches along the main chain, galactomannans have considerable industrial potential. Galactomannans, guar, locust bean, tara and fenugreek gums are the biomacromolecules that have received the most attention for their potential value for a variety of applications, either in their original or modified forms. To expand their application, physically modified galactomannans with enhanced characteristics have been researched as new biomaterials. Consequently, various treatments including ultrasonication, microwave, gamma and ultraviolet radiation, pulsed and induced electric field, high hydrostatic pressure, high pressure homoge-nization, extrusion and electrospinning have successfully been applied to manipulate macromolecules properties, some of these methods reduced their molecular weight. The main theory, techniques, and developments of these technologies, as well as their impact on galactomannan properties, are comprehensively reviewed in this study. From the systematic point of view of the literature, ultrasonic and radiation applications were the most applied and investigated methods in the depolymerization of galactomannans which induced the most promising al-terations in biopolymers. Future research needs, current problems, and practical solutions linked to the use of these novel methodologies in optimum process parameters for galactomannan functionality and improvement should be extensively investigated.
Keywords: Depolymerization; Galactomannan; Modification; Physical treatments; HIGH HYDROSTATIC-PRESSURE; INITIAL MOLECULAR-WEIGHT; PULSED ELECTRIC-FIELDS; GRANULAR POTATO STARCH; LOCUST BEAN GUM; GUAR-GUM; ULTRASONIC DEGRADATION; RHEOLOGICAL PROPERTIES; ACID-HYDROLYSIS; PHYSICOCHEMICAL PROPERTIES; Chemistry; Food Science & Technology